(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study on implementer’s ratings of resource challenges facing Office Technology and Management (OTM) programme in polytechnics in South-East, Nigeria, was necessitated by the need to enhance the quality and product of the programme. Four research questions guided the study and four hypotheses were tested. The study adopted a descriptive survey research design. The population of the study comprised 92 OTM lecturers in all the six polytechnics offering OTM programme in South-East, Nigeria. The entire population was used for the study because the size was small and manageable; therefore, there was no sampling. A self structured questionnaire was developed by the researcher titled “Questionnaire on Resource Challenges facing Office Technology and Management Programme”. The instrument was face validated by three experts. The instrument was trial tested using Cronbach Alpha to calculate the internal consistency of the instrument and an overall reliability index of 0.83 was obtained. Arithmetic mean and standard deviation was used to answer the research questions, while t-test was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed that the implementers strongly agreed that resource challenges facing OTM programme in the SouthEast, Nigeria include: ICT, material, humanand instructional resources. Furthermore, institution ownership significantly influenced implementers’ ratings on human resource challenges only. Based on these findings, it was recommended among others that modern ICT equipment and facilities required inteaching Office Technology and Management courses should be adequately provided to enhance teaching and learning in OTM programme.